Research advances and challenges in tissue-derived extracellular vesicles - Zhi, Zhengke; Sun, Qiaochu; Tang, Weibing (Frontiers in Molecular Biosciences, 2022)
Extracellular vesicles (EV) are vesicular vesicles with phospholipid bilayer, which are present in biological fluids and extracellular microenvironment. Extracellular vesicles serve as pivotal mediators in intercellular communication by delivering lipids, proteins, and RNAs to the recipient cells. Different from extracellular vesicles derived from biofluids and that originate from cell culture, the tissue derived extracellular vesicles (Ti-EVs) send us more enriched and accurate information of tissue microenvironment. Notably, tissue derived extracellular vesicles directly participate in the crosstalk between numerous cell types within microenvironment. Current research mainly focused on the extracellular vesicles present in biological fluids and cell culture supernatant, yet the studies on tissue derived extracellular vesicles are increasing due to the tissue derived extracellular vesicles are promising agents to reflect the occurrence and development of human diseases more accurately. In this review, we aimed to clarify the characteristics of tissue derived extracellular vesicles, specify the isolation methods and the roles of tissue derived extracellular vesicles in various diseases, including tumors. Moreover, we summarized the advances and challenges of tissue derived extracellular vesicles research.